Expulsion of foreigners in Mexico: a commentary on the new “administrative procedure of exclusion” proposed by President Enrique Peña Nieto under the reglementary act of article 33 of the Constitution / Expulsão de estrangeiros no México:... - Vargas, Jorge A. (REVISTA QUAESTIO IURIS, 2015)
DOI:http://dx.doi.org/10.12957/rqi.2015.16907 Trabalho enviado em 28 de abril de 2015. Aceito em 24 de maio de 2015. <p class="Paragraph SCX130241273" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Abstract <p class="Paragraph SCX130241273" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX130241273" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">This study problematizes the expulsion of foreigners in México: a commentary on the New “Administrative Procedure of Exclusion” proposed by President Enrique Peña Nieto under the Reglementary Act of Article 33 of the Constitution. The Constitution of Mexico was profoundly influenced by the Constitution of the United States, and most of the “Individual guarantees” are derived from the U.S. Constitution. During the 19th and 20th centuries, Mexico was deferential to the use and philosophical meaning of the legal expression Garantías Individuales. This explains why Article 1 in Chapter I of the Constitution –formed by 29 articles- was titled: The Individual Guarantees. However, the long legal deference given to the term “Individual guarantees” was somewhat abandoned in 2011 when the then President of Mexico, Felipe Calderón Hinojosa, decided to change the name of Chapter I of the Constitution by means of a decree published in the Diario Oficial de la Federación (DOF) on June 10, 2011. This decree, inter alia, substituted the traditional term of “Garantías Individuales” for the new concept of “Derechos Humanos.” As a result the transatlantic and intercontinental migrations are a particularly useful example for illustrating the importance of international context in the development of the law because of the different ways each governmental body responded to the social pressures. This study shows how the multiple and complex intergovernmental regulatory networks relating to the mobility of this labor force developed in an international context, not solely within the development of isolated national legal systems. The fundamental and welcome revisions made by President Calderon to articles 1 and 33 of the Constitution as a result of his “human rights reform” in 2011 represent some of the most constructive and progressive developments in recognizing, protecting and codifying the rights of foreign persons, a most sensitive topic in the relations between these two neighboring countries. Behind this “human rights reform” one has to think that every year Mexico welcomes over twenty million U.S. tourists that visit that country, who spend some twelve billion dollars during these visits. On the other hand, every year more than one million undocumented Mexicans enter the United States. Therefore, it is of fundamental importance for Mexico to provide a fair and expeditious administrative procedure to expel, deport or extradite foreign persons; a procedure that clearly respects the human rights of foreigners in symmetry with the international standards that domestic legislation, international treaties and conventions, as well as the decisions that international courts have established on this important and delicate area. There is no doubt that the administrative procedure established by President Peña Nieto pursuant to the Reglementary Act o54f Article 33 of the Political Constitution may be characterized today as one of the most fair, modern and advanced procedures for the expulsion of foreign persons at the international level. <p class="Paragraph SCX130241273" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX130241273" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Keywords: Expulsion of foreigners. Mexico. Administrative Procedure of Exclusion. Reglementary Act of Article 33 of the Constitution. Human rights reform. Resumo Este estudo problematiza a expulsão de estrangeiros no México: um comentário sobre o Novo "Procedimento Administrativo de Exclusão" proposto pelo presidente Enrique Peña Nieto ao abrigo da Reglementary Act do artigo 33 da Constituição. A Constituição do México foi profundamente influenciada pela Constituição dos Estados Unidos, e a maioria das "garantias individuais" são derivadas da Constituição dos EUA. Durante os séculos XIX e XX, o México foi deferente ao uso e significado filosófico da expressão legal Garantías Individuales. Isso explica por que o artigo 1 no Capítulo I, da Constituição - formada por 29 artigos- foi intitulado: As garantias individuais. No entanto, a longa deferência legal dada ao termo "garantias individuais" foi um pouco abandonado em 2011, quando o então presidente do México, Felipe Calderón Hinojosa, decidiu mudar o nome do Capítulo I da Constituição por meio de um decreto publicado no Diario Oficial de la Federación (DOF), em 10 de junho de 2011. Este decreto, inter alia, substituído o termo tradicional de "Garantías Individuales" para o novo conceito de "Direitos Humanos". Como resultado as migrações transatlânticas e intercontinentais são um exemplo particularmente útil para ilustrar a importância do contexto internacional no desenvolvimento da lei por causa das diferentes maneiras como cada órgão governamental respondeu às pressões sociais. Este estudo mostra como as múltiplas e complexas redes reguladoras intergovernamentais em matéria de mobilidade dessa força de trabalho desenvolvidas em um contexto internacional, não apenas no âmbito do desenvolvimento dos sistemas jurídicos nacionais isolados. As revisões fundamentais e de boas-vindas feito pelo presidente Calderon aos artigos 1 e 33 da Constituição, como resultado de sua "reforma de direitos humanos" em 2011 representam alguns dos desenvolvimentos mais construtivos e progressistas, em reconhecer, proteger e codificar os direitos das pessoas estrangeiras, um tema mais sensível nas relações entre estes dois países vizinhos. Por trás dessa "reforma de direitos humanos" tem de se pensar que todos os anos, acolhe o México mais de vinte milhões de turistas norte-americanos que visitam esse país, que gastam cerca de doze mil milhões de dólares durante essas visitas. Por outro lado, a cada ano mais de um milhão de mexicanos sem documentos tentam entrar nos Estados Unidos. Portanto, é de fundamental importância para o México fornecer um procedimento administrativo equitativo e rápido para expulsar, deportar ou extraditar pessoas estrangeiras; um procedimento que respeite claramente os direitos humanos dos estrangeiros em simetria com as normas internacionais de que a legislação nacional, os tratados e convenções internacionais, bem como as decisões que os tribunais internacionais estabeleceram nesta área importante e delicada. Palavras-chave: Expulsão de estrangeiros. México. Procedimento Administrativo de Exclusão. Reglementary Act do artigo 33 da Constituição. Reforma dos direitos humanos.1